Clinical and Economic Consequences of Early Cancer After Kidney Transplantation in Contemporary Practice. Issue 4 (April 2017) - Dharnidharka, Vikas R.; Naik, Abhijit S.; Axelrod, David; Schnitzler, Mark A.; Xiao, Huiling; Brennan, Daniel C.; Segev, Dorry L.; Randall, Henry; Chen, Jiajing; Kasiske, Bertram; Lentine, Krista L.
Abstract : Background: Current clinical and economic consequences of cancer after kidney transplantation are incompletely defined. Methods: We examined United States Renal Data System records of Medicare-insured kidney transplant recipients in 2000 to 2011 to determine clinical and economic impacts of cancer diagnosed within the first 3 years posttransplantation. Cancer diagnoses were identified using Medicare billing codes and categorized as nonmelanoma skin cancer (NMSC), viral-linked and "other" cancers. Associations of cancers with mortality and graft loss were estimated by time-varying Cox regression. Impacts of cancer diagnoses on inpatient and outpatient costs within each year were quantified by multivariate linear regression modeling. Results: Among 67 157 recipients, by 3 years posttransplant, NMSC was diagnosed in 5.7%, viral-linked cancer in 1.9%, and "other" cancers in 6.3%. Viral-linked cancer was associated with more than 3-fold increased risk in subsequent mortality until the third transplant anniversary, and nearly twice the mortality risk after year 3. "Other" cancers had similar associations with death and graft loss, whereas NMSC was associated with 33% higher mortality beyond the third year posttransplant. Viral-linked cancer had the largest inpatient and outpatient cost impacts per case, followed by "other" cancer, whereas NMSC impacted only outpatient costs. Care of new cancer diagnoses was generally more costly than care of previously established diagnoses. Cancer accounted for 3% to 5.5% of total inpatient Medicare expenditures and 1.5% to 3.3% of outpatient expenditures in the first 3 years posttransplant. Conclusions: Early posttransplant malignancy is an expensive and morbid condition that warrants attention in efforts to improve pretransplant screening and management protocols before and after transplant. Abstract : Pretransplant cancer screening and improvement of management protocols before and after transplant reduce an expensive treatment cost and improve poor outcome of recipients with early posttransplant de novo malignancy within the first 3 years. Supplemental digital content is available in the text.